Argument structure and the eventive-stative alternation in extent verbs - Gibert-Sotelo, Elisabeth; Marín, Rafael (Glossa (London), 2024)
This study focuses on a group of so-called extent verbs (Gawron 2009) in Spanish (cf. rodear 'surround', cubrir 'cover', or bordear 'border') that show an alternation between an eventive and a stative reading, related to an argument structure alternation: they are eventive with Initiator subjects (i.e., Agents or Causers), but stative with non-Initiator subjects. As we demonstrate, the eventive version has a composite denotation, including a change of state and a subsequent (target) state (Kratzer 2000). The stative version, in turn, describes a state that corresponds to the target state included in the denotation of the eventive version. We offer a non-derivational account of this alternation following Ramchand's (2018) neo-constructionist approach to argument/event structure. Based on a series of diagnostics, we claim that extent verbs can be associated with two different structural configurations that are clearly connected: one which lacks the subeventive projections that introduce causativity (Init) and eventivity (Proc), expressing a non-causative state (State) that extends along a delimited path (Path + Place); and one which, in addition to this stative component, also conveys causation and eventivity (Init + Proc), giving rise to a telic change of state. In both cases, the external argument is licensed by a dedicated projection (Evt), but it is configurationally interpreted, in the former case, as the entity that ensures that the state holds and, in the latter, as an Initiator. The proposal has theoretical implications regarding (non-)agentivity, causativity, the locus of the external argument, and the availability of verbal and adjectival passives.